Grazing incidence X-ray diffraction and transmission electron microscopy studies on the oxide formation of molybdenum in a water vapor environment. (15th July 2016) - Tang, Ming; Nelson, Andrew T.; Wood, Elizabeth S.; Maloy, Stuart A.; Jiang, Ying-Bing
Abstract: To evaluate the feasibility of molybdenum as light water reactor nuclear fuel cladding, the oxidation behavior was tested in water vapor at elevated temperatures. In this study, we present experimental results on the oxidation and volatilization of molybdenum using various characterization techniques including grazing incidence X-ray diffraction and transmission electron microscopy. After oxidation testing in water vapor at 600 °C, experiment results show the formation of both MoO3 and MoO2 . With the increasing temperature, MoO2 is the final oxidation product between 800 and 1200 °C, and MoO3 is volatile at these temperatures. Graphical abstract: